PELAKSAAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS FLIPBOOK PADA PEMBELAJARAN SOSIOLOGI SMAN 3 SIMPANG HILIR KAYONG UTARA - Yuliani, Enik; Ramadhan, Iwan (Dinas Pendidikan dan Kebudayaan Kabupaten Kubu Raya Provinsi Kalimantan Barat, 2025)
This study aims to examine the implementation of the Problem-Based Learning (PBL) model using Flipbook media in Sociology learning. The use of technology is intended to improve the quality of education. Based on preliminary observations, Sociology teachers still tend to be less effective in carrying out the learning process; as a result, students are also less active during Sociology lessons and many of them do not comply with the instructions given by the teacher. Teachers need to innovate by applying more creative and engaging learning methods. One learning model that can encourage students to be more active and think critically in the learning process is the Problem-Based Learning model. At SMA Negeri 3 Simpang Hilir, the use of media in the learning process is still lacking due to limited understanding of emerging technologies. One of the media previously used is Flipbook. The research method employed is qualitative with a descriptive approach. The implementation of Sociology learning using the Problem-Based Learning model with Flipbook media was carried out in two sessions. The results of the study show that teachers assessed students in three domains: the knowledge domain, in which students were evaluated based on group and individual assignments reflecting their knowledge and daily life experiences; the attitude domain, in which students were assessed on their responsibility (such as attending classes), spiritual and social attitudes; and the skills domain, in which students were assessed on their collaboration, inclusion of facts, examples, and theories, as well as politeness and creativity.